Monsters 21 stories of the most fantastic and gruesome creatures of all time : with exercises for developing reading comprehension and critical thinking skills - Billings, Henry (Critical reading series, 1999)
Nonfiction articles about mythical beasts including the cyclops, King Kong, the Jersey Devil, Medusa, Bigfoot, the Loch Ness monster, Scylla and Charybdis, Frankensteins's monster, giants, the minotaur, Grendel, Dracula, Chupacabra, werewolves, zombies, and dragons. Each is followed by reading comprehension and critical thinking exercises.